KAJIAN INDUSTRI GULA MERAH TEBU DI NAGARI LAWANG KECAMATAN MATUR KABUPATEN AGAM - Meira Putri; deded Chandra (JURUSAN GEOGRAFI FIS UNP, 2021)
This study aims to determine the effect of production factors in terms of capital and land area as well as the marketing area of ​​the sugar cane industry in Nagari Lawang, Agam District, Matur District, Agam Regency. This type of research is descriptive with a quantitative approach. The sample in this study was the owner of the brown sugar cane industry. Data collection techniques using observation, questionnaires, interviews and documentation. Data analysis techniques through data tabulation using normality test, linear regression test and hypothesis testing. The results of the research findings are as follows: (1) The production factor starts from the initial capital which comes from personal capital and the results of the t test show that capital has a significant effect on the income of the owner of the brown sugar cane industry (Sig 0.001 <0.05) with an initial capital of Rp. 40.000.000-120.000.000. (2) The land area has a significant effect on the production of brown sugar cane with the normality test results showing Lo <Lt, namely 0.1165 <01195 and thus the land data (X2) is normally distributed and is followed by the results of the linear regression test which shows that the P-Value is 0 , 01 <0.05. The significance value (Sig) is smaller (<) than the 0.05 probability, this means that there is an influence. The decision obtained is that the land area (X2) has a significant effect on sugarcane production (Y) because the significant value is 0.01 <0.05. (3) The marketing areas for the Nagari Lawang brown sugar cane, Matur District, Agam Regency, are mainly in the Lawang area itself and are also scattered in West Sumatra provinces, namely Padang, Sijunjung, Solok, Pariaman, Payakumbuh, Bukittinggi, Batu Sangkar, and also outside West Sumatra, namely Pekanbaru.